African Queens find mates when males are rare. Issue 4 (2nd April 2023) - Rutagarama, Vincent P.; Ireri, Piera M.; Sibomana, Constantin; Omufwoko, Kennedy S.; Martin, Simon H.; ffrench‐Constant, Richard H.; Eckardt, Winnie; Kaplin, Beth K.; Smith, David A. S.; Gordon, Ian
Abstract: In butterflies and moths, male‐killing endosymbionts are transmitted from infected females via their eggs, and the male progeny then perish. This means that successful transmission of the parasite relies on the successful mating of the host. Paradoxically, at the population level, parasite transmission also reduces the number of adult males present in the final population for infected females to mate with. Here we investigate if successful female mating when males are rare is indeed a likely rate‐limiting step in the transmission of male‐killing Spiroplasma in the African Monarch, Danaus chrysippus . In Lepidoptera, successful pairings are hallmarked by the transfer of a sperm‐containing spermatophore from the male to the female during copulation. Conveniently, this spermatophore remains detectable within the female upon dissection, and thus, spermatophore counts can be used to assess the frequency of successful mating in the field. We used such spermatophore counts to examine if altered sex ratios in the D. chrysippus do indeed affect female mating success. We examined two different field sites in East Africa where males were often rare. Surprisingly, mated females carried an average of 1.5 spermatophores each, regardless of male frequency, and importantly, only 10–20% remained unmated. This suggests that infected females will still be able to mate in the face of either Spiroplasma ‐mediated male killing and/or fluctuations in adult sex ratio over the wet–dry season cycle. These observations may begin to explain how the male‐killing mollicute can still be successfully transmitted in a population where males are rare. Abstract : African Queens or Monarchs can still find males even in the face of extensive male‐killing. This finding has unexpected implications for the fitness and maintenance of the male‐killing endosymbiont Spiroplasma .